Engineering education applications - Rosales-Anzola, Sergio D.; Pérez-Hernández, Miguel M. (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The applications developed to virtualize the laboratory of fluids and transfers of the Metropolitan University are presented. The aim was to allow students to perform laboratory practices online. An application of each practice was developed using MATLAB App Designer. The students were able to perform each virtual practice by manipulating the corresponding variables in real time and obtaining the results with which to make the reports. These applications were used to teach the course virtually, obtaining good acceptance by the students, who felt each practice was interactive and useful for their learning process.